DAMPAK GREEN INVESTMENT, PENGUNGKAPAN ESG DAN FINANCIAL PERFORMANCE TERHADAP NILAI PERUSAHAAN PERBANKAN DI INDONESIA - Sri Andriani (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
Sustainability is a crucial issue because it relates to the integration of environmental, social, and governance (ESG). Companies are not only focused on increasing profitability and corporate value but also strive to achieve sustainability through environmentally friendly products (green products). This study aims to determine the impact of green investment, ESG disclosure, and financial performance on the value of banking companies in Indonesia. The analysis uses panel data regression on companies included in the SRI-KEHATI index from 2020 to 2024. The results show that partially, green investment, ESG disclosure, and financial performance have an insignificant influence on the value of banking companies in Indonesia. However, simultaneously, green investment, ESG disclosure, and financial performance have a significant influence on the value of banking companies in Indonesia.